EKSTRAK BUNGA WARU (Hibiscus tiliaceus) SEBAGAI INDIKATOR ASAM-BASA - Frantauansyah, Frantauansyah; Nuryanti, Siti; Hamzah, Baharuddin (Universitas Tadulako, 2013)
Hibiscus tiliaceus is a tribe or cottons malvacea, it is known as sea hibiscus. This plant has been known for a long time ago. It is known as a shade tree in the curb or in the edge of the river and as the embankment along the coast. Although, the canopy is not too dense, it is preferred because its roots are not deep into the soil. So, it does not damage the roads and buildings. This study of hibiscus flower extract has been done. It proved that there was indicator acid-base. Hibiscus flower washed with distilled water, cut into small piece, then add dissolved acetate ethyl and macerated. After that, filtered and residue re-extracted filtering results with absolute ethanol. Extract filtered by using gauze filter, then filtered it again with paper filter paper. The filtrate is ready to use as as acid-base indicator. After that, evaluated with benchmark indicators phenolphthalein and orange methyl to titrate acid-base such as: a strong base with a strong acid, a weak base with a strong acid and a strong base with a weak acid. The result of survey revealed that the indicator of hibiscus flower extracts indicate the equivalence point in the titration result equivalent to the comparison indicator. The result showed the indicator of the hibiscus flower extract can as a substitute to synthetic indicator (phenolphthalein and orange methyl) has been used.